Flashback of The Khawarij Stream in History: From Its Inception To The Distortion Of Its Teachings - Anggraheni, Umi Septina; Nurhuda, Abid; Al Anang, Arif; Maghfuroh, Ana; Anugrah, Dena Sri (Institute of Research and Public Service Universitas Jenderal Soedirman, 2024)
When the Prophet Muhammad was still alive, there were rarely any divisions among Muslims because he was a source of solutions in knowledge and charity when a problem occurred. However, when he died, little by little problems began to emerge that could not be resolved and the culmination occurred in the Siffin War, resulting in the emergence of various theological schools, one of which was the Khawarij. So this research aims to describe the flashbacks of the Khawarij sect in historical history. The method used is qualitative with a literature study approach and then analyzed descriptively. The results of the research show that the Khawarij sect emerged since there was a political conflict between Ali's ranks and Mu'awiyah's troops who held abstruse (tahkim) in the siffin war. Apart from that, in its development, the main doctrines of the Khawarij sect covered the ideological and social fields. From there, several prominent figures were born, including 'Abd al-Karim bin 'Ajrad the founder of the Al-'Ajaridah sect, Nafi'bin Al-Azraq the founder of Al-Azariqah, Ziad ibn Al-Ashfar the founder of Al-Shafariyah, Najdah bin Amir as the founder of Al-Najadat, and Abdullah bin Ibadh as the founder of Al –Ibadhiyyah. The most striking deviant teaching of the Khawarij sect is that it is easy to consider someone who is outside their group as an infidel, even though one creed condemns that person as having committed a major sin so that they deserves to be put in hell.